Density and distribution of dendritiform cells in the peripheral cornea of healthy subjects using in vivo confocal microscopy - Akhlaq, Anam; Colón, Clara; Cavalcanti, Bernardo M.; Aggarwal, Shruti; Qazi, Yureeda; Cruzat, Andrea; Jersey, Candice; Critser, Douglas B.; Watts, Amy; Beyer, Jill; Sindt, Christine W.; Hamrah, Pedram (The ocular surface, 2022)
To establish in a large healthy cohort, dendritiform cell (DC) density and morphological parameters in the central and peripheral cornea using in vivo confocal microscopy (IVCM). A prospective, cross-sectional, observational study was conducted in 85 healthy volunteers (n = 85 eyes). IVCM images of corneal center and four peripheral zones were analyzed for DC density and morphology to compare means and assess correlations (p < 0.05 being statistically significant). Central corneas had lower DC density (40.83 ± 5.14 cells/mm2; mean ± SEM) as compared to peripheral corneas (75.42 ± 2.67 cells/mm2, p < 0.0001). Inferior and superior zones demonstrated higher DC density (105.01 ± 7.12 and 90.62 ± 4.62 cells/mm2) compared to the nasal and temporal zones (59.93 ± 3.42 and 51.77 ± 2.98 cells/mm2, p < 0.0001). Similarly, lower DC size, field and number of dendrites were observed in the central as compared to the average peripheral cornea (p < 0.0001), with highest values in the inferior zone (p < 0.001 for all, except p < 0.05 for number of dendrites in superior zone). DC parameters did not correlate with age or gender. Inter-observer reliability was 0.987 for DC density and 0.771–0.922 for morphology. In healthy individuals, the peripheral cornea demonstrates higher DC density and larger morphology compared to the center, with highest values in the inferior zone. We provide the largest normative cohort for sub-stratified DC density and morphology, which can be used in future clinical trials to compare differential changes in diseased states. Furthermore, as DC parameters in the peripheral zones are dissimilar, random sampling of peripheral cornea may be inaccurate. [Display omitted] •Peripheral corneas have higher DC density than central corneas in healthy individuals.•In peripheral corneas, inferior and superior zones have highest DC density.•Peripheral corneas have a higher DC area, field and number of dendrites than the center.•Inferior peripheral zones have the highest DC area, field and number of dendrites.•Random sampling of peripheral corneas should not be performed, unless compared to the same area.